Volunteering for development in Egypt: examining the benefits of student volunteering on skills development and employability - Ali, Amira (AUC Knowledge Fountain, 2013)
The purpose of this empirical study is to investigate the extent to which volunteering at the university level in Egypt has an impact on skill development and employment opportunities for graduates. In the first part, the scope and nature of student volunteering in Egypt is identified as well as the motives, barriers and benefits of student volunteering. The perceived impact of student volunteering is assessed with regards to personal development, transferrable skills, and employability. In the second part of the study, the value of volunteering to Egyptian employers is examined to indicate the extent to which volunteering could increase graduates employability. For the first part of the study, a total of 335 public and private university students were surveyed in the area of Greater Cairo. Student volunteers and non-volunteers responded to a questionnaire on the perceived motives, barriers, and benefits of student volunteering. The descriptive results indicate that volunteering has a positive impact on personal development, transferrable skills, and future employability. For the second part of the study, a total of 50 employers in both the public and private sectors were surveyed to assess the value of volunteering and whether it increases future employability. The descriptive results indicate that volunteering equip students with the skills demanded by employers. The results indicate that the most important soft skills to Egyptian employers are communication skills, time management, teamwork, computer literacy, and flexibility. Out of the top five skills demanded by employers, volunteering has been found to improve competence at three important skills namely communication, teamwork, and flexibility. Also, volunteering was found to improve a candidates' image to employers and has a positive effect on employability. The findings reflect a need to encourage and promote student volunteering at the university level to improve graduates' skills and employment opportunities.